Discovery of circa 115,000-year-old bone retouchers at Lingjing, Henan, China. - Luc Doyon; Zhanyang Li; Hao Li; Francesco d'Errico (PLoS ONE, 2018)
Most Chinese lithic industries dated between 300,000 and 40,000 are characterized by the absence of Levallois debitage, the persistence of core-and-flake knapping, the rarity of prepared cores, their reduction with direct hard hammer percussion, and the rarity of retouched flakes. Here we report the discovery of seven bone soft hammers at the early hominin Lingjing site (Xuchang County, Henan) dated to 125,000-105,000. These artefacts represent the first instance of the use of bone as raw material to modify stone tools found at an East Asian early Late Pleistocene site. Three types of soft hammers are identified. The first consists of large bone flakes resulting from butchery of large herbivores that were utilized as such for expedient stone tools retouching or resharpening. The second involved the fracture of weathered bone from medium size herbivores to obtain elongated splinters shaped by percussion into sub-rectangular artefacts. Traces observed on these objects indicate intensive and possibly recurrent utilization, which implies their curation over time. The last consists of antler, occasionally used. Lingjing bone tools complement what we know about archaic hominin cultural adaptations in East Asia and highlight behavioural consistencies that could not be inferred from other cultural proxies. This discovery provides a new dimension to the debate surrounding the existence of the Middle Palaeolithic in the region. The attribution of East Asian sites to the Middle Palaeolithic assumes that cultural traits such as the Levallois method represent evolutionary hallmarks applicable to regions of the world different from those in which they were originally found. Here, we promote an approach that consists in identifying, possibly from different categories of material culture, the original features of each regional cultural trajectory and understanding the behavioural and cognitive implications they may have had for past hominin populations.